Patient-important benefits of clearing the hepatitis C virus through treatment: A simulation model - Innes, Hamish; Goldberg, David; Dusheiko, Geoffrey; Hayes, Peter; Mills, Peter R.; Dillon, John F.; Aspinall, Esther; Barclay, Stephen T.; Hutchinson, Sharon J. (Journal of hepatology, 2014)
Given an appreciable risk of adverse-effects, current therapies for chronic hepatitis C virus (HCV) infection pose a dilemma to patients. We explored, via simulation modelling, patient-important benefits of attaining a sustained viral response (SVR). We created the HCV Individualised Treatment-decision model (the HIT-model) to simulate, on a per patient basis, the lifetime course of HCV-related liver disease according to two distinct scenarios: (i) SVR attained, and (ii) SVR not attained. Then, for each model subject, the course of liver disease under these alternative scenarios was compared. The benefit of SVR was considered in terms of two patient-important outcomes: (1) the percent-probability that SVR confers additional life-years, and (2) the percent-probability that SVR confers additional healthy life-years, where “healthy” refers to years spent in compensated disease states (i.e., the avoidance of liver failure). The benefit of SVR varied strikingly. It was lowest for patients aged 60years with initially mild fibrosis; 1.6% (95% CI: 0.8–2.7) and 2.9% (95% CI: 1.5–4.7) probability of gaining life-years and healthy life-years, respectively. Whereas it was highest for patients with initially compensated cirrhosis aged 30years; 57.9% (95% CI: 46.0–69.0) and 67.1% (95% CI: 54.1–78.2) probability of gaining life-years and healthy life-years, respectively. For older patients with less advanced liver fibrosis, SVR is less likely to confer benefit when measured in terms of averting liver failure and premature death. These data have important implications. Foremost, it may inform the contemporary patient dilemma of immediate treatment with existing therapies (that have poor adverse effect profiles) vs. awaiting future regimens that promise better tolerability.